Fishing in troubled waters? Strategic decision‐making and value creation and appropriation from partnerships between public organizations. (19th November 2018) - van den Oever, Koen; Martin, Xavier
Abstract : Research Summary : Although partnerships have been conceptualized as vehicles for value creation, less is known about which partners appropriate more value out of them, especially among public organizations. We theorize how politics and procedural rationality in decision‐making respectively are associated with value creation and value appropriation from partnerships between public organizations. Analysis of data from the Dutch water authority sector (2008–2014) shows that organizations employing more politics in decision‐making appropriate more value from horizontal partnerships, whereas procedural rationality in decision‐making may enhance combined value creation but limits partner‐level value appropriation. Also as theorized, the collective decision‐making context constrains value appropriation by partners using a discrepant decision‐making approach. We discuss implications for research on public organizations, alliances, and strategic decision‐making. Managerial Summary : Although much is known about how partnerships can create value for firms, we know relatively less about which of the partners can appropriate more value from them. In this paper, we theorize and find that (public) organizations that employ more politics in decision‐making can generally appropriate more value from partnerships. Organizations that are more procedurally rational, which entails the extensive collection and analysis of information to make decisions, are able to create more value for the partnership, but generally appropriate less value from the partnership. Moreover, an organization that has a different decision‐making approach than its partners' end up appropriating less value from the partnership. Thus, when forming partnerships, managers should carefully consider the way their potential partners make decisions.